Hvordan de blev til: Vikingetidens stilgrupper fra Broa til Urnes - Klæsøe, Iben Skibsted (Hikuin, 2002)
How They Came To Be Viking-period style groups from Broa to Urnes By Iben Skibsted Klæsøe The history of scholarship relating to the styles of the Viking Period is rather different from that of the Germanic art styles. The individual Viking art styles have been defined over the course of many years, some of them only recently, and continue to be debated. However for this period as for the Germanic Iron Age, it was Müller who fired the starting shot. Plant ornament appears as a distinct but limited style in the early Viking Period. In connexion with the construction of a new chronology for the Viking Period the author has nonetheless based herself on this type of decoration. It was subsequently of decisive importance to the development of the animals of the Mammen and Ringerike Styles. In stylistic terms, the transition from the Germanic Iron Age to the Viking Period involved a series of very different styles and concepts, which overlap with one another and often occur side-byside. The Continental Tassilo Style, a product of the Insular mission to the Continent, has been recognized since Müller’s time, and for a long time was called the Missionary Style; it was defined as the Tassilo Style by Haseloff in 1951. Style F was regarded by Ramskou (1965) as a southern Scandinavian derivative of the Tassilo Style. These styles are dated to the second half of the 8th century and around 800. The Broa Style was Almgren’s term from 1955 for the later manifestations of Salin’s Style III, described in 1904, and is practically the same as Arwidsson’s Style E of 1942. Association with gripping beasts is characteristic of some of the material in this style. These gripping beasts were something quite new in Scandinavian animal art. They came to leave their mark both on the Berdal brooches and on the later Borre Style. The Broa Style/Style E is dated to the final third of the 8th century. The »Oseberg masters« is Shetelig’s term for the woodcarvers who produced the carved wooden objects in and on the Oseberg ship. These wooden artefacts are stylistically very diverse and comprise several of the styles of the transitional period. Dendro-datings assign the boat to the year 820 and the burial chamber to 834. Gripping beasts are a feature found in the Broa, the Berdal and the Borre Styles and are therefore contemporary with all of these. They were identified by Rydh in 1919, and have since been the subject of much discussion because of their lack of predecessors in Scandinavian art. Most recently (2001) Helmbrecht has questioned whether a Continental origin is plausible. The Berdal Style, which is found on oval (tortoise) brooches, moulds for which have been found in large numbers in the Ribe excavations, is in fact only regarded as a distinct style by Capelle and the present author. The studies of the moulds from Ribe date the Berdal brooches and the gripping beasts found upon them to the last quarter of the 8th century. The most recent research on this particular style has been carried out by Wamers, who sees it as entirely the product of influence from Continental cloisters, with the Anglo-Irish mission and the Carolingian Renaissance. Helmbrecht, however, has identified certain chronological problems. The present author has suggested that the whole style group involving the early gripping beasts should be treated as one under the title of the Asymmetrical Style. The Borre Style involves gripping beasts and much besides. Shetelig assigned both the finds from Borre and those from Gokstad to this category and regarded it as a derivative of the Oseberg Style. The Borre Style has been widely used as a portmanteau term for 9th-century material. The present author has suggested redefining this style and its contents and calling it the Symmetrical Animal Style. The subsequent animal styles are no longer based upon gripping beasts but upon ribbon-shaped and heraldic-looking, standing beasts and »the large animal«. The Jellinge Style, which Müller had identified but which was only christened by Shetelig, involves ribbon-shaped animals seen in profile. This style is dated to the first half of the 10th century. The present author has suggested using the term Profile Animal Style for the Jellinge Style. In 1931, Lindqvist distinguished the Mammen Style from the Jellinge Style. Characteristic of this is a large animal seen in profile and associated with a limited amount of plant ornament. Birds are also found in considerable numbers. The Mammen Style is dated to the second half of the 10th century. This style has most recently been discussed by Wamers in connexion with a new publication of the great Jellinge stone. While the Jellinge Style is regarded as of Anglo-Saxon inspiration, the Mammen Style is attributed to both Ottonian influences and the Winchester Style. The Ringerike Style involves animals of many different kinds, as well as human figures and masks, while scenic views are also known. This style was identified by Shetelig as a later development of the Mammen Style and it is extensively associated with plant ornament. It was in fact first distinguished from the Mammen Style by Lindqvist in 1931. The most thorough examination of the style is that by Fuglesang in 1980, which attributed it to aristocratic circles and the newly established Church in Scandinavia, as a development reflecting Continental and possibly Anglo-Saxon influence, including, once again, the Winchester Style. The Urnes Style, the last of the animal-art styles, developed out of the Ringerike Style and is based upon the large animal. Typical of this style are animals with very long and thin extremities. Shetelig had identified this style as early as 1909, and it is particularly well known for its occurrence on Norwegian stave-churches. The most recent comprehensive studies are those of Fuglesang from 1992 and Wilson of 1995. Fuglesang sees an Anglo-Saxon background and a logical association with the Church, while Wilson believes that the style is quite different from its predecessors. This style is dated from around the middle of the 11th century to a point within the 12th century. The Viking-period styles merge into one another, and this makes it a difficult job to classify the material. Many scholars have worked with individual styles but only a few have looked at them as a whole sequence. The sharpest boundary falls between the earlier Viking Period and the later – between the gripping beast and the heraldiclooking, standing animal: to be more precise, between Borre and Mammen. Between these two styles – and contemporary with the later manifestations of the Borre Style – came the Jellinge Style. This style, which is characterized by snake- and bird-like animals seen in profile, is quite independent and has no link with the other Viking art styles. On the contrary, several elements can be seen to be congruent with the Style F of about a hundred years earlier.